Efficient In/SSZ-39 catalysts for the selective catalytic reduction of NO with CH4 - An, Sufeng; Wang, Peng; Wang, Kuanling; Wang, Xuehai; Li, Baozhong; Guo, Xinwen (Frontiers in Chemistry, 2024)
The M/SSZ-39 catalysts (M = In, Co, Cu, Fe) with different metal species and metal loadings were synthesized using the wet impregnation method on a small-pore SSZ-39 molecular sieve. X-ray diffraction (XRD), transmission electron microscopy (TEM), nitrogen adsorption-dehydrogenation and hydrogen temperature program reduction (H2-TPR) were employed to characterize the effects of various metal components and metal loadings on the performance of CH4 selective catalytic reduction of NO reaction (CH4-SCR). The characterization results showed that the In/SSZ-39 catalyst exhibited significantly higher catalytic activity compared to the Cu-, Co-, and Fe/SSZ-39 catalysts, suggesting that indium (In) is a more suitable active ingredient for the CH4-SCR reaction. The xIn/SSZ-39 (x = 1, 2, 3, x represents the In loadings of 1.0 wt%, 2.0 wt% and 3.0 wt%) catalysts, with different In loadings, all present excellent CH4-SCR performance. By varying the In loadings, the type of In species present in the catalyst can be regulated, thus enhancing DeNOx activity and CH4 selectivity in the CH4-SCR reaction. At a low temperature of 400 ℃ and a low CH4/NO feed ratio (CH4/NO = 1), the 3In/SSZ-39 catalyst, featuring highly active InOx clusters, achieves the best low-temperature CH4-SCR performance, with a high NO conversion rate of up to 90% and a CH4 selectivity of up to 74.2%.